OsSIDP301, a Member of the DUF1644 Family, Negatively Regulates Salt Stress and Grain Size in Rice - Ge, Li; Guo, Hongming; Li, Xiu; Tang, Ming; Guo, Chiming; Bao, Han; Huang, Linjuan; Yi, Yin; Cui, Yuchao; Chen, Liang (Frontiers in Plant Science, 2022)
As a major environmental factor, salt stress substantially retards growth and reduces the productivity of rice (Oryza sativa). Members of the DUF1644 family ‘the domains of unknown function 1644 motif’ are predicted to play an essential regulatory role in response to abiotic stress. However, the specific molecular mechanisms of most members of this family remain elusive. Here, we report that the OsSIDP301 (Stress-induced DUF1644 protein) was induced by salt stress and abscisic acid (ABA). We found that overexpression of OsSIDP301 (OE) plants conferred salt hypersensitivity and reduced grain size, whereas OsSIDP301 RNA interference (RNAi) plants exhibited salt tolerance and increased grain size in rice. OsSIDP301 determines salt stress tolerance by modulating genes involved in the salt-response and ABA signaling pathways. Further studies suggest that OsSIDP301 regulates grain size by influencing cell expansion in spikelet hulls. Moreover, OsSIDP301 interacts with OsBUL1 COMPLEX1 (OsBC1), which positively regulates grain size in rice. Our findings reveal that OsSIDP301 functions as a negative regulator of salt stress and grain size, and repressing its expression represents a promising strategy for improving salt stress tolerance and yield in rice.